Mali : Fifth Review Under the Extended Credit Facility and Request for Extension, Augmentation of Access and Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Mali. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper provides a review of Mali's economic performance under the Extended Credit Facility (ECF) and requests for extension, augmentation of access, and modification of performance criteria. The political situation has continued to stabilize, following the signing of the peace agreement in June 2015. On the macroeconomic side, the recovery continued in 2015, with strong GDP growth, low inflation, and strengthening of the fiscal position. Overall, program implementation in 2015 was strong. All performance criteria and indicative targets for the fifth review were observed, generally with significant margins. The authorities are requesting a one-year extension of the current ECF arrangement, to December 2017.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet